Caracterización del licopeno extraído de la corteza del tomate riñón variedad Daniela (Lycopersicum esculentum L.) en la Universidada Estatal de Bolívar - Quincha Rodriguez, Evelyn Carolina (2017)
Due to the importance that has been given to compounds with antioxidant activity, in this research it was considered important to obtain lycopene from the dehydrated tomato variety Daniela variety, it was started by the physical characterization (moisture and Ash) of the raw material, whose results were evaluated in three replicates, giving an average value of 85.12% for moisture, 3.23 % for ash. The application of the different temperatures (30, 40 and 50 ° C) of dehydration of the tomato cortex and times (1 and 2 hours) of lycopene extraction in the soxhlet equipment resulted in the treatment T5 being the highest Quantity of sample (11, 2 mg/100 g) at the temperature of 50 ° C and 1 hour followed by the treatment T6 (10, 8 mg/100 g) at the temperature of 50 ° C and 2 hours. Temperature and time controlled variables are one of the important factors in the extraction of tomato lycopene, depending on the amount of solvent used. The evaluation of the purity of the lycopene was performed by high performance liquid chromatography (HPLC), which process showed the best treatment for T3, corresponding to a temperature of 40 ° C and a time of one hour for extraction by soxhlet. This treatment showed less inference in the chromatogram of other compounds such as xanthophylls and carotenes. The economic analysis in the cost benefit relation of the best treatment according to the amount of sample obtained.